2020
DOI: 10.2500/aap.2020.41.200078
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and natural history of food protein‐induced enterocolitis syndrome in the east Mediterranean region

Abstract: Background: Food protein‐induced enterocolitis syndrome (FPIES) is a rare non-IgE mediated food allergy. Objective: To delineate the differences in the spectrum of culprit foods, remission patterns, and predictors among varying cultures. Methods: We reviewed demographics, culprit foods, outcomes, and predictors in 81 children with a diagnosis of FPIES who were followed up between 2015 and 2020. Results: Eighty-one patients (55.6% boys) were enrolled, including 72 with acute FPIES and 9 with chronic FPIES.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
1
12
2
2
Order By: Relevance
“…Limited data suggest that atypical FPIES with positive specific IgE is associated with delayed tolerance 6,8,16 . This was not confirmed in our study population, like in the recent Swedish 29 and Greek cohorts, 44 although sensitization (IgE and/or SPT; 14.7%) were similar compared to other studies (11.1%–34%) 10,11,18,22,25,26 . Atopic disorder was found in 41% of patients and eczema in 29%.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Limited data suggest that atypical FPIES with positive specific IgE is associated with delayed tolerance 6,8,16 . This was not confirmed in our study population, like in the recent Swedish 29 and Greek cohorts, 44 although sensitization (IgE and/or SPT; 14.7%) were similar compared to other studies (11.1%–34%) 10,11,18,22,25,26 . Atopic disorder was found in 41% of patients and eczema in 29%.…”
Section: Discussioncontrasting
confidence: 87%
“…This may result from the use of stringent criteria for the diagnosis of FPIES and the retrospective design of the study. Despite medical charts studied, for multiple FPIES in 13.4% of cases as per other series, 13,17,25,27,29‐31 we only retained FPIES with a specific clinical description. The prevalence of multiple FPIES ranges from 5.1% 19 to 69.0% 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the main culprit food was CM, followed by hen's egg, and fish, which differs from the findings in other countries. [7][8][9][10][11][12] The most frequent culprit food was fish in Greece 13 and Spain 10,14 rice in Australia [15][16][17] and the USA, 18 and oats in Taiwan. 19 Soy is frequently reported as a trigger food by North American, British, Australian and Israeli cohorts 4,17,20,21 and was infrequent in our population.…”
Section: Discussionmentioning
confidence: 99%
“…From a geographically diverse population of 441 children with FPIES, data provided by caregivers in the International FPIES Association showed that fish was the third lowest in the hierarchy of offending foods [ 58 ]. In contrast, reports from Mediterranean countries, specifically Greece [ 8 , 9 , 10 ], Italy [ 2 , 3 ], Spain [ 1 , 4 , 5 , 6 , 7 , 16 , 59 ], and Turkey [ 60 ] revealed fish as the first or second most commonly implicated food and a major trigger of solid food protein allergy. It has also been concluded that the resolution of fish-FPIES comes later than that from other foods [ 61 ], and many children with fish-FPIES will not overcome the disease during childhood [ 62 ].…”
Section: Food Protein-induced Enterocolitis Syndrome (Fpies) Caused By Fishmentioning
confidence: 99%